Mangifera Indica mid-rib fibers as reinforcements for CNSL-epoxy composites. Issue 4 (17th March 2022) - Shenoy Heckadka, Srinivas; Nayak, Suhas Yeshwant; Samant, Rashmi
Abstract: This research work explores the potential of Mangifera indica leaf mid-rib fibers as a reinforcement for polymer composites. The fibers were subjected to sodium bicarbonate treatment for 6 h, 12 h, 18 h, and 24 h duration and the effect of chemical treatment on the tensile strength of the fibers was evaluated. Maximum tensile strength of 104 MPa was obtained for 18 h treated fibers. Scanning electron microscopy of the fiber surface revealed surface impurities, layers of dead cells and degradation of fibrils, as some of the important features for variation in tensile strength. Fourier transform infrared spectra of all varieties of fibers supported function group modifications with chemical treatment. X-ray diffraction analysis of the fiber confirmed improvement in the crystallinity index of the fibers till duration of 18 h. Composites with untreated and 18 h treated fibers were considered for fabrication along with Cashew Nut Shell Liquid (CNSL)/epoxy matrix. Techniques such as hand layup and compression moulding were adopted for composite fabrication and mechanical properties of the cured composites were determined. Maximum values of tensile, flexural and impact strength obtained were 48 MPa, 70 MPa and 38 kJ/m 2 respectively. Failure modes such as fiber pull-out, fiber shearing, fiber debonding and matrix shearing were observed through scanning electron micrographs of the Mangifera indica composites.